Physical and Chemical Properties of Soil, Water and Air around Ukawu Pb-Zn Mine, Southeastern Nigeria - Nwachukwu, Nwachukwu Arthur; Udie, Sikakwe Gregory; Nchedo, Eluwa Ndidiamaka; Ukamaka, Uwa Clementina; Olaosebikan, Oluwatoyin Oluwatosin (Makara Journal of Science, 2021)
In this study, analysis of water, and soil samples, air quality, and noise levels in Ukawu Pb-Zn mine were examined. The pH of the water samples, at 6.7, exceeded permissible levels for potable water established by the National Environmental Standard Regulatory Agency (NESREA), European Union, and World Health Organization (i.e., 7.0-8.5). The soil pH was 5.2, which indicates acidity due to acid mine drainage. Low soil pH is evidence of acid mine drainage. All cations detected in water and soil were below standard limits considered harmful by the NESREA. Measurements of precursor gases, such as O3, NO2, CO and SO2, to determine air quality showed levels below the air quality standards prescribed by the NESREA. Thus, the air quality around the mine is not polluted by these gases. Noise levels around the mine were below the 85dB limit considered deleterious to humans. Comparison of the noise levels detected around the mine with Indian showed that the values obtained in Ukawu mine exceed the permissible daytime values for industrial, commercial, residential, and silence zones. This research could serve as a benchmark for environmental contamination studies at the regional and global scales.